Root and tuber crops in the Caribbean - Ferguson, T.U. (International Center for Tropical Agriculture, 1986)
The importance and production of root crops in 17 Caribbean countries are analyzed. Statistical data on the production and per capita production of the following root crops are given: yam, cassava, sweet potato, taro, cocoyam, and potato. Cassava is the major root crop grown (734,000 t in 1982-83), followed by sweet potato (551,000 t). Cuba, Dominican Republic, and Haiti are the largest cassava growing countries, and Cuba, Grenada, Haiti, and St. Vincent have the largest per capita production. Constraints to research, training, production, and utilization for each crop are discussed. Finally, the importance of a regional research network on root crops is stressed, its objectives are indicated, and possible project activities are listed. (CIAT)